Time to first and recurrent missed video directly observed therapy sessions and associated factors among people with Tuberculosis in Kampala, Uganda - Kelvin Bwambale; Drake Amutuheire; Damalie Nakkonde; Patrick Kaggwa; Esther Buregyeya; Sarah Zalwango; Sarah Nabukeera; John B. Isunju; Juliet N. Sekandi (Frontiers in Digital Health, 2026)
Background Video Directly Observed Therapy (VDOT) provides a promising alternative to in-person directly observed therapy (DOT) for Tuberculosis (TB) treatment adherence monitoring. However, sustained patient engagement and missed video submissions remain a challenge. This study examined the time to first and recurrent missed VDOT submissions and the associated factors. Methods We conducted a retrospective cohort analysis study of 71 people with TB assigned to the VDOT arm of the DOT Selfie randomized trial in Kampala, Uganda. Primary outcomes were time to first and recurrent missed VDOT sessions, analyzed using the Kaplan–Meier estimator. Associated factors were identified with Cox regression and the Prentice-Williams-Peterson Gap Time model. Median times with corresponding first and third quartiles (Q1, Q3) and adjusted hazard ratios (aHRs) with their 95% Confidence Intervals were reported. Analyses were conducted in Stata 14·2. Results Of the 71 participants, 36 (51%) were female, the median age was 29 years (24, 42), and 23 (32%) were living with HIV. The median time to the first missed VDOT session was 9 days (2, 39), and to recurrent missed sessions was 2 days (1, 8). Earlier first missed sessions were associated with HIV co-infection (aHR=1·99; 95% CI: 1·09, 3·62), being married (aHR = 1·88; 95% CI: 1·03, 3·42), and reporting alcohol use (aHR=4·11, 95% CI: 1·89, 8·97). Factors associated with earlier recurrences of missed sessions included being currently married (aHR = 1·34; 95% CI: 1·03, 1·75) compared to the never married. A larger household size was slightly protective against earlier recurrent missed sessions (aHR = 0·96; 95% CI: 0·92, 0·99). Conclusion This study highlights the factors that are associated with earlier missed VDOT sessions in the Ugandan setting. These factors may help identify groups that could benefit from targeted adherence support in future VDOT implementation efforts. We recommend more research to understand the interplay of marital status with VDOT use.